Comparative study on divorce under Muslim Law and Civil Law / Mariani Ghani - Ghani, Mariani (Faculty of Law, 1985)
This paper primarily deals with divorce law under the Islamic Law and the Civil Law comparatively.The first chapter is the introduction to the chapter. In the chapter, the writer discussed the purpose of divorce law under Islamic Law and Civil Law. Divorce is the solution of a dead lock when marriage can no longer be uphold. The continuance of unhappy marriage would likely ruin the lives of the parties. eventhough the aim of marriage is to last for life.